Africa’s manufacturing puzzle: Evidence from Tanzanian and Ethiopian firms - Diao, Xinshen; Ellis, Mia; McMillan, Margaret S.; Rodrik, Dani (International Food Policy Research Institute, 2021)
Recent growth accelerations in Africa are characterized by increasing productivity in agriculture, a declining share of the labor force employed in agriculture and declining productivity in modern sectors such as manufacturing. To shed light on this puzzle, we disaggregate firms in the manufacturing sector by size using two newly created panels of manufacturing firms, one for Tanzania covering 2008-2016 and one for Ethiopia covering 1996-2017. Our analysis reveals a dichotomy between larger firms that exhibit superior productivity performance but do not expand employment much, and small firms that absorb employment but do not experience any productivity growth. We suggest the poor employment performance of large firms is related to use of capital-intensive techniques associated with global trends in technology.